2018
DOI: 10.2478/jvetres-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Dinophysis species and associated okadaic acid in farmed shellfish: a two-year study from the western Mediterranean area

Abstract: IntroductionDiarrhoetic shellfish poisoning (DSP), an alimentary intoxication known to lead to intestinal symptoms, and caused by toxins produced by some dinoflagellates (including several Dinophysis), represents a serious threat to public health. The aim of this paper was to provide information about the occurrence and abundance of potentially toxic harmful algal species causing DSP, and the associated concentration of okadaic acid (OA) toxins. The departing assumption was that in the study area there was an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…Many authors have reported and analysed the possible causes of the discrepancy between the values for toxicity in molluscs and the abundance of microalgae [24,32,33,34]. The causes mainly proposed are the presence of alternative food, environmental factors, the stratification of the water column that favours the development of thin layers of microalgae, or the variability in the toxin content per cell.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported and analysed the possible causes of the discrepancy between the values for toxicity in molluscs and the abundance of microalgae [24,32,33,34]. The causes mainly proposed are the presence of alternative food, environmental factors, the stratification of the water column that favours the development of thin layers of microalgae, or the variability in the toxin content per cell.…”
Section: Discussionmentioning
confidence: 99%
“…In SGL, during 2015 no algae were detected in each episode of OA accumulation and no data about previous HAS were available (since they were collected only concurrently with OA accumulation over the legal limits). But considering dynamics in FER and data in literature (Bazzoni, et al ., 2018 ), we may hypothesise that algae were present even many weeks before OA accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The different phases of extraction and analysis with LC-MS/ MS are reported specifically in Bazzoni et al . ( 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Okadaic acid (OA) is a toxin produced by various species of dinoflagellates and can cause food poisoning in humans after consumption of contaminated molluscs [45]. An automated flow-through electrochemical immunosensor was developed for OA determination in mussel samples.…”
Section: Screen-printed Electrodes (Spes) For Voltammetric Immunosmentioning
confidence: 99%